Testing a novel audit and feedback method for hand hygiene compliance: A multicenter quality improvement study. (15th November 2018) - Scherer, Aaron M.; Reisinger, Heather Schacht; Goto, Michihiko; Goedken, Cassie Cunningham; Clore, Gosia S.; Marra, Alexandre R.; Chasco, Emily E.; Evans, Charlesnika T.; Rubin, Michael A.; Perencevich, Eli N.
Abstract: Objective: Although most hospitals report very high levels of hand hygiene compliance (HHC), the accuracy of these overtly observed rates is questionable due to the Hawthorne effect and other sources of bias. In the study, we aimed (1) to compare HHC rates estimated using the standard audit method of overt observation by a known observer and a new audit method that employed a rapid (<15 minutes) "secret shopper" method and (2) to pilot test a novel feedback tool. Design: Quality improvement project using a quasi-experimental stepped-wedge design. Setting: This study was conducted in 5 acute-care hospitals (17 wards, 5 intensive care units) in the Midwestern United States. Methods: Sites recruited a hand hygiene observer from outside the acute-care units to rapidly and covertly observe entry and exit HHC during the study period, October 2016–September 2017. After 3 months of observations, sites received a monthly feedback tool that communicated HHC information from the new audit method. Results: The absolute difference in HHC estimates between the standard and new audit methods was ~30%. No significant differences in HHC were detected between the baseline and feedback phases (OR, 0.92; 95% CI, 0.84–1.01), but the standard audit method had significantly higher estimates than the new audit method (OR, 9.83; 95% CI, 8.82–10.95). Conclusions: HHC estimates obtained using the new audit method were substantially lower than estimates obtained using the standard audit method, suggesting that the rapid, secret-shopper method is less subject to bias. Providing feedback using HHC from the new audit method did not seem to impact HHC behaviors.